Functional movement scores and longitudinal performance outcomes in elite track and field athletes - Chapman, R. F.; Laymon, A. S.; Arnold, T. (International Journal of Sports Physiology and Performance, 2014)
Subjects with scores on the Functional Movement Screen (FMS) assessment of =14 or with at least 1 bilateral asymmetry have been shown to have greater future injury incidence than subjects with FMS scores >14 or no movement asymmetries. Purpose: To determine if FMS injury risk factors extend to longitudinal competitive performance outcomes in elite track and field athletes. Methods: Elite track and field athletes were examined (N = 121), each completing an FMS before the 2011 competitive season. Best competition marks for the year were obtained from athletes` actual performances for 2010 and 2011. Performance change between 2010 and 2011 was examined in cohorts of FMS scores =14 (LoFMS) vs >14 (HiFMS), athletes with bilateral asymmetry in at least 1 of the 5 FMS movements vs athletes with no asymmetry, and athletes who scored 1 on the deep-squat movement vs athletes who scored 2 or 3. Results: HiFMS had a significantly different change in performance from 2010 to 2011 (0.41% ± 2.50%, n = 80) compared with LoFMS (-0.51% ± 2.30%, P = .03, n = 41). Athletes with no asymmetries had a longitudinal improvement in performance (+0.60% ± 2.86%, n = 50) compared with athletes with at least 1 asymmetry (-0.26% ± 2.10%, P = .03, n = 71). Athletes who scored 1 on the deep-squat movement had a significantly different change in performance (-1.07 ± 2.08%, n = 22) vs athletes who scored 2 (0.13% ± 2.28%, P = .03, n = 87) or 3 (1.98% ± 3.31%, P = .001, n = 12). Conclusion: Functional movement ability, known to be associated with the likelihood of future injury, is also related to the ability to improve longitudinal competitive performance outcomes.